Prerequisites for the development of human capital of the construction industry - Shovkivska, V. (Ways to Improve Construction Efficiency, 2018)
This article reveals the influence of the main factors on the human capital development. The main indicators of the labor market as a basic condition for the use and development of human capital are considered. The role of human capital development in improving the efficiency of construction industry production is shown.